Peningkatan Literasi Remaja Dalam Pencegahan Perkawinan Anak Di Kalangan Pelajar SMAN 1 Bluto Kabupaten Sumenep - Rillia Aisyah Haris; Imam Hidayat; Anita . (Fakultas Sosial dan Ilmu Politik Universitas Wiraraja, 2025)
Child marriage remains a serious problem in various regions in Indonesia. Although Law No. 16 of 2019 sets the minimum age for marriage at 19 for both men and women, the practice of early marriage remains common, particularly among adolescents. Adolescents, particularly high school students, are at a critical stage in their psychosocial development. They are beginning to form their identities, but often lack the knowledge and skills to make important decisions regarding their future, including marriage. In this context, improving adolescent literacy, including reproductive health, legal literacy, social literacy, and critical literacy, is key to preventing them from falling into child marriage. SMAN 1 BLUTO was chosen because Bluto District is one of the districts with the highest child marriage rates in Sumenep Regency. Through this community service activity, it is hoped that adolescents will improve their understanding of the negative impacts of child marriage, from health, educational, social, and economic perspectives. This activity also aims to equip adolescents with critical thinking skills and the ability to make responsible decisions regarding their future. With a participatory and contextual educational approach, schools become a strategic space for instilling child protection values ​​and awareness of the importance of delaying marriage for a better future.